Governance for Justice and Environmental Sustainability Lessons across natural resource sectors in sub-Saharan Africa - Sowman, Merle; Wynberg, Rachel (Taylor & Francis, 2014)
The intention of this book is to begin to shed light on these issues, by exploring the interplay between governance, justice and sustainability in a range of natural resource sectors. The book comprises 16 chapters, 12 of them case studies recounting experiences in the forest, wildlife, fisheries, conservation, mining and water sectors of diverse countries: Madagascar, Zimbabwe, Botswana, Namibia, South Africa, Zambia, Mozambique, Sierra Leone and Cameroon.